Context Matters: Teaching Styles and Basic Psychological Needs Predicting Flourishing and Perfectionism in University Music Students - Herrera, Dora; Matos, Lennia; Gargurevich, Rafael; Lira, Benjamín; Valenzuela, Rafael (Frontiers in Psychology, 2021)
Professional musicians are expected to perform at a very high level of proficiency. Many times, this high standard is associated with perfectionism, which has been shown to prompt both adaptive and maladaptive motivational dynamics and outcomes among music students. The question of how perfectionism interplays with motivational dynamics in music students is still unanswered and this research line is scarce, especially in Latin America. Perfectionism can be conceptualized as a trait-like individual characteristic or as a result of adapting to contextual influences; consequently, it could act as a predictor of need satisfaction/frustration and well-being/flourishing, or it could be a by-product of how the music student perceives the motivational style of the teacher. Using Self-Determination Theory (SDT), this cross-sectional study investigated the relationship between the perceptions of motivational context (teachers’ motivating styles: autonomy supportive or controlling), basic psychological needs (satisfaction/frustration), perfectionism (adaptive/maladaptive), and flourishing in university music students from Lima, Peru (N = 149; mean age = 20.68, SD = 3.03; 71% men). We performed two path analyses testing competing models: Model A, in which only motivational teaching styles predicted both perfectionism and flourishing via need satisfaction/frustration, and Model B, in which perfectionism, alongside teaching styles, predicted flourishing via need satisfaction. The best fitting model, as expected, was Model A, which considered perfectionism and flourishing as outcomes of motivational teaching styles via need satisfaction/frustration, (χ2 (10, N = 143) = 12.44, p = .143. CFI = .992, TLI = .978, RMSEA = .041, SRMR = .050). In this model, perceived autonomy supportive style predicted need satisfaction positively and need frustration negatively; perceived controlling teaching style did not predict need satisfaction nor frustration. In turn, need satisfaction positively predicted adaptive perfectionism (i.e. high standards) and flourishing; whereas, need frustration predicted maladaptive perfectionism (i.e. discrepancy). These results shed light on the relevance of perfectionism in the psychology of higher music education students. Lastly, we highlight the importance of autonomy support in fostering adaptive high standards in music learning.